The Investigation of the Physical and Performance Effects of High-Intensity Interval Training (HITT) on Sedentary University Students - Cigerci, Ali Erdem; Genc, Harun (Canadian Center of Science and Education, 2020)
The aim of this study was to examine the physical and selected performance characteristics of 9-week High-Intensity Interval Training (HIIT) on sedentary university students. Participants were separated two groups as HIIT and control group (CG). HIIT group applied training 3 times a week for 9 weeks. CG was not applied any training. Before and after HIIT training program, the subjects were applied to age, height, body weight (BW), body mass index (BMI) tests for physical parameters and standing long jump (SLJ), vertical jump (VJ), 10-20 m sprint, T agility test (TAT), star excursion balance test (SEBT), running-based anaerobic sprint test (RAST) for performance parameters. Multiple analysis of variance (MANOVA) was used to analyze of inter-group, intra group and the effect of training in repeated measurements. Bonferroni test was used for Post Hoc comparisons; the significance level was accepted as 0.05. There was a significant difference in BW, BMI and all performance parameters in favor of HIIT group. HIIT provided effective development to physical and performance characteristics of university students.
Keywords: 4. Education